2013
DOI: 10.1093/nar/gkt381
|View full text |Cite
|
Sign up to set email alerts
|

Scalable web services for the PSIPRED Protein Analysis Workbench

Abstract: Here, we present the new UCL Bioinformatics Group’s PSIPRED Protein Analysis Workbench. The Workbench unites all of our previously available analysis methods into a single web-based framework. The new web portal provides a greatly streamlined user interface with a number of new features to allow users to better explore their results. We offer a number of additional services to enable computationally scalable execution of our prediction methods; these include SOAP and XML-RPC web server access and new HADOOP pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
1,046
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,259 publications
(1,078 citation statements)
references
References 18 publications
26
1,046
2
4
Order By: Relevance
“…Representations of individual Nups and some of their subcomplexes (Supplementary Table 2 and references therein) relied on (1) atomic structures of 21 yeast Nup domains and 3 sub-complexes determined by X-ray crystallography or NMR spectroscopy; (2) our structures of Nup116, Nup133, Nup145N, Nup192, and Pom152, as well as the Nup82 and Nup84 sub-complexes solved by integrative structure determination 43,66,72,8892 ; (3) 29 comparative models built with MODELLER 9.13 108 based on the known structure(s) detected by HHPred 109,110 and the literature; (4) SAXS profiles for 147 constructs of 18 Nups 43,72,8892 (Supplementary Table 6; manuscript in preparation); (5) secondary structure, disordered regions, and domain boundaries predicted by PSIPRED 111,112 , DISOPRED 113 , and DomPred 114 , respectively; (6) coiled-coil regions of Nup82, Nup159, Nsp1, Nup49, Nup57, Mlp1, and Mlp2 predicted by COILS/PCOILS 115 and Multicoil2 116 ; (7) an atomic structure of the Nup53 229–365 RRM domain from S. cerevisiae determined by X-ray crystallography (manuscript in preparation); and (8) the negative-stain EM density maps of full-length Nup192 (EMD-5556 92 ) and Pom152 (EMD-8543 43 ). See Supplementary Table 2 and references therein.…”
Section: Methodsmentioning
confidence: 99%
“…Representations of individual Nups and some of their subcomplexes (Supplementary Table 2 and references therein) relied on (1) atomic structures of 21 yeast Nup domains and 3 sub-complexes determined by X-ray crystallography or NMR spectroscopy; (2) our structures of Nup116, Nup133, Nup145N, Nup192, and Pom152, as well as the Nup82 and Nup84 sub-complexes solved by integrative structure determination 43,66,72,8892 ; (3) 29 comparative models built with MODELLER 9.13 108 based on the known structure(s) detected by HHPred 109,110 and the literature; (4) SAXS profiles for 147 constructs of 18 Nups 43,72,8892 (Supplementary Table 6; manuscript in preparation); (5) secondary structure, disordered regions, and domain boundaries predicted by PSIPRED 111,112 , DISOPRED 113 , and DomPred 114 , respectively; (6) coiled-coil regions of Nup82, Nup159, Nsp1, Nup49, Nup57, Mlp1, and Mlp2 predicted by COILS/PCOILS 115 and Multicoil2 116 ; (7) an atomic structure of the Nup53 229–365 RRM domain from S. cerevisiae determined by X-ray crystallography (manuscript in preparation); and (8) the negative-stain EM density maps of full-length Nup192 (EMD-5556 92 ) and Pom152 (EMD-8543 43 ). See Supplementary Table 2 and references therein.…”
Section: Methodsmentioning
confidence: 99%
“…2c). Predictions of protein secondary structure generated by using the online PSIPRED tool (Jones 1999;Buchan et al 2013) suggested that Leu635 is located within an a-helix (Fig. 2d).…”
Section: Single Amino Acid Substitutions In Lipinmentioning
confidence: 99%
“…Utilizing the DISOPRED Prediction Server, this repeat motif is predicted to be disordered in contrast to PBL13's kinase domain ( Fig. 1C; Ward et al, 2004;Buchan et al, 2013). The multiple metastable conformations that are adopted by disordered proteins are hypothesized to facilitate target recognition with high specificity and low affinity (Marín et al, 2013).…”
Section: Pbl13 Is An Rlck VII With Unique Domain Architecturementioning
confidence: 99%
“…Intrinsic disorder was predicted using the DISOPRED component of the PSIPRED Prediction Server, with the false discovery rate set to 5% (Ward et al, 2004;Buchan et al, 2013).…”
Section: Kinase Motif and Protein Disorder Predictionmentioning
confidence: 99%